Titanium elastic nails vs locking plate in pediatric subtrochanteric femur fractures: A systematic review and meta-analysis - Zhang, Yaqiang; Xue, Yun; Zhao, Maosheng; Chen, Xianxia; Gao, Qiuming (Frontiers in Pediatrics, 2023)
Objective: To systematically evaluate the effectiveness and safety of Titanium elastic nails (TEN) and locking plates (LP) in treating subtrochanteric fractures in children, to provide a theoretical basis and reference for clinical treatment. Methods: The literature related to TEN and locking plates for the treatment of subtrochanteric fractures in children were searched through the CNKI, PubMed, Cochrane, Embase, and Web of science, and the search time frame was from the establishment of the database to October 2022. 2 evaluators screened the literature according to the inclusion and exclusion criteria and extracted relevant data. Meta-analysis was performed using stata14.0 software. Results: A total of 9 studies with 407 patients with subtrochanteric femur fractures were included in the final screening, including 210 cases with TEN and 197 cases with locking plates. Meta-analysis results showed that compared with the locking plate, TEN had a shorter operative time [WMD =-1.3，95%CI(-1.94,-0.66), P＜0.01], P＜0.01], less intraoperative bleeding [WMD =-84.45，95%CI(-111.09,-57.82), P＜0.01], shorter fracture healing time [WMD =-1.3，95%CI(-1.94,-0.66), P＜0.01], shorter hospital day [WMD =-2.80，95% CI(-4.63,-0.98), P＜0.01], and full weight-bearing time earlier [SMD =-0.48，95% CI(-0.91,-0.04), P＜0.05], but more intraoperative fluoroscopy [WMD =28.23，95% CI(15.22,41.25), P＜0.05], the overall complication rate was high [OR =3.52, 95% CI(1.96,6.34), P<0.05], and the postoperative period was prone to angulation, rotation and inversion deformity [0R=3.68, 95% CI(1.40, 9.68), P < 0.05], no significant difference in the incidence of lower limb inequality between the two types of internal fixation [OR = 0.83, 95% CI (0.38, 1.85), P > 0.05], and no significant difference in the Harris score of the hip at the last follow-up between the two types of internal fixation [WMD = -0.67, 95% CI (-2.01,0.67), P > 0.05].Conclusion: TEN has a short operation time, less intraoperative bleeding, and short fracture healing time, and the child can be fully weight-bearing early. The locking plates can reduce the operator's X-ray exposure, and the incidence of postoperative angulation, rotation, and inversion deformity is low. Therefore, TEN and locking plates are the best internal fixation methods for treating subtrochanteric fractures in children.